A Study on the Relationship between Sense of Disease Uncertainty and Family Strength and Mental Resilience in Guardians of Children with Inflammatory Bowel Disease - Jun Yan; Lin Luo (Emergency Medicine International)
Background. Inflammatory bowel disease is difficult to cure, which seriously affects the physical and mental health of children and brings negative psychological stress to guardians. Uncertainty in illness of guardians reduces the ability of care and is not conducive to the treatment and recovery of children. Therefore, it is of great significance to explore the related factors of uncertainty in illness. Objective. The aim of this study is to explore the relationship between sense of disease uncertainty and family strength and mental resilience in guardians of children with inflammatory bowel disease (IBD). Method. A total of 146 guardians of 88 children with inflammatory bowel disease were investigated. The guardians’ sense of disease uncertainty, family strength, and mental resilience were evaluated by Mishel uncertainty in illness scale-family member (MUIS-FM), family hardiness index (FHI), and Connor–Davidson resilience sca1e (CD-RISC), respectively. Spearman correlation was used for analyzing the correlation between the guardian’s sense of disease uncertainty and family resilience. Results. The guardian’s MUIS-FM score from lowest to highest was complexity, unpredictability, lack of information, and uncertainty. The average scores of FHI and CD-RISC were lower than the average score of CD-RISC of the general community in China 65.4 (t = −4.36, P<0.05). The score of MUIS-FM was significantly correlated with the scores of FHI and CD-RISC (P<0.05). Multiple linear regression analysis showed that the challenge score in the FHI scale and the fortitude score and the strength score in the CD-RISC scale were the main influencing factors of guardians’ sense of disease uncertainty in children with IBD (P<0.05). Conclusion. The guardians of children with IBD had a more serious sense of disease uncertainty, which was related to family strength and mental resilience.